Follow-up protocol for newborns of birthweight less than 1500 g or less than 32 weeks gestation - Carmen Pallás Alonso; Pilar García González; Ana Jimenez Moya; Begoña Loureiro González; Yolanda Martín Peinador; Javier Soriano Faura; María José Torres Valdivieso; Gemma Ginovart Galiana (Elsevier, 2018)
The mortality of children with a birthweight of less than 1500 g or with a gestational age of less than 32 weeks (<1500 < 32) has decreased significantly in the last 20 years or so. Given the higher risk of disability in these children, follow-up after hospital discharge is considered essential. In this document, the Follow-Up Group of the Spanish Society of Neonatology, in collaboration with the Spanish Society of Paediatric Primary Care, propose a follow-up protocol specific for the <1500 < 32, which has as its aim to standardise the activities and evaluations according to good practice criteria. Resumen: La mortalidad de los niños nacidos con peso menor de 1.500 g o con una edad gestacional menor de 32 semanas (<1.500 < 32) ha disminuido significativamente en las últimas décadas. Dado el mayor riesgo de discapacidad de estos niños, el seguimiento tras el alta hospitalaria se considera muy necesario. En este documento, el Grupo de Seguimiento de la Sociedad Española de Neonatología, en colaboración con la Asociación Española de Pediatría de Atención Primaria, propone un protocolo de seguimiento específico para los < 1.500 < 32, cuyo objetivo es estandarizar las actividades y evaluaciones según los criterios de buena práctica.